Policy Coordination under Model Disagreement and Uncertainty - Carsten Hefeker; Michael Neugart (Center for Economic Studies and ifo Institute (CESifo), 2019)
What are the incentives for governments to coordinate their policies internationally when there is model disagreement and uncertainty? We build a model where countries disagree on policy targets and how policies affect the economies, and show that uncertainty not only determines the type of cooperative policy but also whether countries want to cooperate at all. Countries facing larger model disagreement also need to face larger uncertainty with respect to policy spillovers to agree on cooperation. Thus, uncertainty on spillovers can be a substitute for model agreement.
Keywords: F42; F53; F55; F68; 330; policy coordination; uncertainty; ideological commitment; model disagreement